Effect of the addition of hydrocolloids on beef texture: Targeted to the needs of people with dysphagia. (April 2021) - Pematilleke, Nelum; Kaur, Mandeep; Rai Wai, Carleen Tse; Adhikari, Benu; Torley, Peter J.
Abstract: This study evaluated the effect of addition of 14 different hydrocolloids that are commonly used in meat industry as texture modifiers, with a view to screen and categorise, hydrocolloid added beef patties within the International Dysphagia Diet Standardisation Initiative (IDDSI) levels of modified textures. Beef patties were made with 1% formulation for each hydrocolloid and were compared with control (no added hydrocolloid) samples. The effects were studied individually on cooking properties, colour and texture of beef patties, and samples were tested for compliance with the IDDSI guidelines. All hydrocolloids significantly (P < 0.05) increased the cooking yield of beef patties except modified corn starch. Compared to the control, diameter reduction was not significant in all treatments except for carboxymethyl cellulose (CMC) and xanthan gum. Patty texture was significantly (P < 0.05) altered with the addition of hydrocolloids by mostly decreasing hardness and cohesiveness. Adhesiveness increased with gum based and decreased with starch based hydrocolloids. Treatment of hydrocolloids brought lighter (L*) and yellower (b*) colour to the patties without significantly affecting the redness (a*) and pH of raw patties. Only two treatments (CMC and xanthan gum) complied with the IDDSI fork pressure test by squashing meat with the application of pressure and not returning to its original shape when pressure is released, thus categorised as potential level 6 (soft & bite-sized) diet in the IDDSI framework. However, both of these hydrocolloids at 1% concentration did not give a proper structure to beef patties therefore further optimization of the beef patty mixture is recommended to develop patties with acceptable quality. Graphical abstract: Image 1 Highlights: Hydrocolloids (1%) altered texture, colour, diameter and cooking yield of beef patties. CMC and xanthan gum added beef patties were suitable as IDDSI level 6 food. Poor structure and lightness increase were observed in CMC and xanthan gum added beef patties.